1995
DOI: 10.1029/94ja02036
|View full text |Cite
|
Sign up to set email alerts
|

Theory and observation of auroral substorms: A magnetohydrodynamic approach

Abstract: A theory of auroral substorm dynamics is constructed on the basis of MHD wave processes in the ionosphere-magnetosphere system. The basic view is that the substorm commences in the nightside near-Earth magnetosphere through a collapse of plasma equilibrium. The collapse releases a significant amount of free energy embedded initially in a collection of compressional waves. It is suggested that substorm dynamics after the collapse are determined by the evolution of these waves. We first investigate the quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 36 publications
(15 reference statements)
2
43
1
Order By: Relevance
“…The source of energy for monochromatic, ULF FLRs is believed to be compressional, near-monochromatic fast MHD waves formed in magnetospheric waveguides or cavities (Samson et al, 1992a;Liu et al, 1994). This is still a very active area of study, and results are not conclusive.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The source of energy for monochromatic, ULF FLRs is believed to be compressional, near-monochromatic fast MHD waves formed in magnetospheric waveguides or cavities (Samson et al, 1992a;Liu et al, 1994). This is still a very active area of study, and results are not conclusive.…”
Section: Introductionmentioning
confidence: 90%
“…This cutoff marks the field lines mapping to the inner edge of the electron plasma sheet . These undulations may indicate that the FLR was driven by a magnetotail cavity mode (Liu et al, 1994), not the flank MHD waveguide postulated by Samson et al (1992a). The apparent westward propagation (cf.…”
Section: Observations Of the Night-side Flrs Eventsmentioning
confidence: 99%
“…As shown by J. Samson and his group, both from observational and theoretical grounds (see Samson et al, 1992;Samson and Rankin, 1994;Rankin et al, 1994;Liu et al, 1995), non-linear standing lowfrequency waves in the mHz range can be intimately related to the arcs' formation and their multiplicity. In this theory the resonances are fed by broad-band noise in the system, and it was shown that auroral electrons accelerated by FA electric field due to large k ⊥ in the Alfven wave can reach typical auroral energies in a steady state.…”
Section: Non-linear Standing Alfven Waves In the Mhz Range And Multipmentioning
confidence: 99%
“…Finally we may comment about the model developed by Samson et al (1992) and Liu et al (1995), which considers the slow time evolution of a homogeneous arc. We suppose that the MFM could be a stable location of a slowly oscillating arc.…”
Section: Comparisons With the Gvz92 Modelmentioning
confidence: 99%
“…Another theory is that being developed by Samson et al (1992) (see also, Liu et al, 1995), stimulated by high resolution ground-based optical observations of arcs from the Canadian CANOPUS network. Oscillations and splitting of homogeneous arcs with periods of order of 10±20 min are often observed, basely distinguishable by the naked eye.…”
Section: Introductionmentioning
confidence: 99%